Analisis Pengaruh Produk, Harga, Dan Lokasi Terhadap Minat Beli Konsumen Pada Toko Foto Copy Nusa Lontar Mola Kelurahan Welai Timur Kecamatan Teluk Mutiara Kabupaten Alor - Maruli, Elia (Peneliti.net, 2025)
Purchase intention is a consumer behavior where consumers have the desire to buy or choose a product based on experience in choosing, using and consuming or even wanting a product. This research aims to determine the influence of product, price and location on consumer buying interest in Photo Copy Nusa Lontar Mola, Welai Timur Village, Teluk Mutiara District, Alor Regency. The sample of this research was 40 consumers. Data collection uses observation, interviews, questionnaires and documentation techniques. The data was then analyzed using multiple linear regression analysis to determine the independent variable (X) against the dependent variable (Y). The results of this research show that, product variables (X1), price variables (X2) and location variables (X3) have a significant effect on consumer buying interest (Y) in Nusa Lontar Mola Photo Copy, East Welai Village, Teluk Mutiara District, Alor Regency, based on the results research, it is recommended that Photo Copy Owners consider product provision, pricing and location determination, so that consumer buying interest in Nusa Lontar Mola Photo Copy automatically increases.